2007
DOI: 10.1097/00006199-200701000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing to Increase Physical Activity in Long-Term Cancer Survivors

Abstract: Use of MI may increase physical activity in long-term cancer survivors, especially in persons with high self-efficacy for exercise. Multilevel modeling analysis revealed individual changes that would not have been shown by analysis of group means. Future studies with larger samples or more intense MI interventions may show changes in aerobic fitness, physical and mental health, and fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
204
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(209 citation statements)
references
References 29 publications
3
204
0
2
Order By: Relevance
“…Motivational interviewing is recognized as an important approach to behavior change in multiple health contexts (Armstrong et al, 2011;Befort et al, 2008;Bennett et al, 2007;Carels et al, 2007;Hardcastle et al, 2008;Heckman et al, 2010;Jenson et al, 2011;Lai et al, 2010;O'Halloran et al, 2014). MI has also been recognised as a complex approach to interventions comprising multiple techniques (Michie et al, 2013;Miller & Rollnick, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivational interviewing is recognized as an important approach to behavior change in multiple health contexts (Armstrong et al, 2011;Befort et al, 2008;Bennett et al, 2007;Carels et al, 2007;Hardcastle et al, 2008;Heckman et al, 2010;Jenson et al, 2011;Lai et al, 2010;O'Halloran et al, 2014). MI has also been recognised as a complex approach to interventions comprising multiple techniques (Michie et al, 2013;Miller & Rollnick, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Motivational interviewing (MI) has been shown to be a promising approach for promoting health behavior change in a number of contexts including substance abuse (Jenson et al, 2011), quitting smoking (Heckman, Egleston, & Hofmann, 2010;Lai, Cahill, Qin, & Tang, 2010), physical activity promotion (Bennett, Lyons, Winters-Stone, Nail, & Scherer, 2007;Carels, Darby, Cacciapaglia, Konrad Coit, & Harper, 2007;Hardcastle, Blake, & Hagger, 2012;Hardcastle, Taylor, Bailey, & Castle, 2008;O'Halloran et al, 2014), and dietary change (Armstrong et al, 2011;Befort et al, 2008). MI can be considered a complex intervention comprising multiple techniques to promote behavior-change.…”
Section: Motivational Interviewingmentioning
confidence: 99%
“…32 Studies have described interventions combining face-to-face with telephone contact with positive outcomes. [33][34][35] For instance, in the UK an RCT with over 300 patients found that a very brief cognitive behavioural therapy (CBT) intervention promoted earlier adjustment to illness among patients at high risk of developing affective disorders. 35 …”
Section: Telephone Counsellingmentioning
confidence: 99%
“…These approaches have shown encouraging results in terms of beneficial changes in physical activity, diet behaviour and/or weight outcomes in the short term (3-month followup) (5)(6)(7) and longer term (6 months to 1 year) (5,6,(8)(9)(10)(11)(12)(13) .…”
mentioning
confidence: 99%